Genetic polymorphism of methylenetetrahydrofolate reductase as a potential risk factor for congenital heart disease: A meta-analysis in Chinese pediatric population. Issue 23 (June 2017) - Yuan, Ye; Yu, Xia; Niu, Fenglan; Lu, Na
Abstract: Background: A meta-analysis of polymorphism C677T (rs1801133) of the methylene tetrahydrofolate reductase (MTHFR) gene as a potential risk factor for congenital heart disease (CHD) in Chinese paediatric population was studied in view of the previously reported controversial results. Methods: We searched literature including PubMed, Embase, Cochrane Library, CNKI, Wanfang, and VIP databases that resulted in the identification of a total of 21 separate studies with 6414 subjects that met the inclusion criteria in the Chinese population. The quality assessment of the included studies was preformed and relevant information was collected. We chose the fixed-effect model or random-effect model to calculate the pooled odds ratio (ORs) and its corresponding 95% confidence interval (95% CI) where appropriate. Begg test was used to measure publication bias and sensitivity analyses were done to ensure authenticity of the outcome. Results: We observed a significant association between MTHFR C677T polymorphism and CHD development in all the genetic models evaluated. The pooled ORs and 95% CIs in all genetic models indicated that children's MTHFR C677T polymorphism was significantly associated with CHD. Conclusion: Our study results indicate that MTHFR gene 677T polymorphism is a genetic risk factor in the development of CHD in Chinese paediatric population.